Annual risk of tuberculosis infection in rural China: a population-based prospective study. Issue 1 (26th May 2016) - Gao, Lei; Bai, Liqiong; Liu, Jianmin; Lu, Wei; Wang, Xinhua; Li, Xiangwei; Du, Jiang; Chen, Xinchun; Zhang, Haoran; Xin, Henan; Sui, Hongtao; Li, Hengjing; et al.
Prospective population data on the incidence of tuberculosis (TB) infection has been sparsely reported in the global literature. A population-based prospective study was conducted in rural China to investigate the annual risk of TB infection, and its persistence using serial tuberculin skin tests (TSTs) and an interferon-γ release assay. In total, 13 580 eligible participants from four rural sites, identified as TST negative (<10 mm) or QuantiFERON-TB Gold In-Tube (QFT) (an interferon-γ release assay) negative from a baseline survey, were included in the first year's follow-up examination. The annual conversion rate of QFT among the study sites ranged between 2.1% and 4.9% (average 3.1%), and the incidence of TST conversion ranged between 6.0% and 31.1% (average 14.5%). During the second year's follow-up, infection persistence was investigated using 390 subjects with QFT conversions. Among them, 49.7% (164 out of 330) were found to be consistently QFT positive. Both the conversion and the persistence of QFT positivity were found to be significantly increased with increasing age. In conclusion, the annual TB infection rate was suggested to be ∼1.5% based on persistent positive results after QFT conversion in rural China. Therefore, infection control among those high-risk populations, including the elderly, should be prioritised for TB control in China. Annual TB infection rate ∼1.5% in rural China, based on persistent positive results after IGRA conversion http://ow.ly/4n95Cw